2010
DOI: 10.1007/s00774-010-0196-x
|View full text |Cite
|
Sign up to set email alerts
|

Risedronate improves proximal femur bone density and geometry in patients with osteoporosis or osteopenia and clinical risk factors of fractures: a practice-based observational study

Abstract: The purpose of this practice-based observational study was to clarify the acute effect of risedronate on proximal femur bone mineral density (BMD) and structural geometry in patients with an increased risk of fractures. One hundred sixty-four patients (7 men and 157 postmenopausal women; mean age, 69.2 years) with osteoporosis or osteopenia and clinical risk factors of fractures were analyzed. All these patients were treated with risedronate for 1 year. Urinary levels of cross-linked N-terminal telopeptide of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…In the SABRE study, femoral BMD increased (?2%) after 2 years of anastrozole and risedronate therapy, whereas it decreased (although not significantly) in similar patients in the ARBI trial [22]. Given that femoral BMD decreased in our patients on anastrozole alone (group A) and did not change in those taking anastrozole and risedronate, anastrozole presumably has a negative effect on femoral BMD as well, whereas risedronate can prevent this BMD loss [23].…”
Section: Discussioncontrasting
confidence: 48%
“…In the SABRE study, femoral BMD increased (?2%) after 2 years of anastrozole and risedronate therapy, whereas it decreased (although not significantly) in similar patients in the ARBI trial [22]. Given that femoral BMD decreased in our patients on anastrozole alone (group A) and did not change in those taking anastrozole and risedronate, anastrozole presumably has a negative effect on femoral BMD as well, whereas risedronate can prevent this BMD loss [23].…”
Section: Discussioncontrasting
confidence: 48%
“…[6][7][8][9][10] We previously reported that 1 year of risedronate therapy significantly increased the BMD of the lumbar spine and femoral neck and improved geometric parameters including the CSMI and CSA. 11) We also reported that 3 years of risedronate therapy maintained or attenuated these improvements in the BMD, CSMI, and CSA. 12) However, very few studies have been performed in which the long-term effects of risedronate were evaluated using DXA incorporated with femoral geometric parameters.…”
mentioning
confidence: 56%
“…At corticocancellous sites, the cortical shell thickness and area increases in osteoporotic women with bisphosphonate treatment [44,45]. For example, risedronate increased the cross-sectional moment of inertia and cross-sectional area of the femur in osteoporotic and osteopenic women and men after 4, 8, and 12 months of treatment [44].…”
Section: Cortical Geometrymentioning
confidence: 99%
“…At corticocancellous sites, the cortical shell thickness and area increases in osteoporotic women with bisphosphonate treatment [44,45]. For example, risedronate increased the cross-sectional moment of inertia and cross-sectional area of the femur in osteoporotic and osteopenic women and men after 4, 8, and 12 months of treatment [44]. In a recent report, however, cortical thickness of the femoral diaphysis was not increased with alendronate treatment for at least 5 years when measured by DXA [46], but DXA has limitations for measuring cortical thickness [47].…”
Section: Cortical Geometrymentioning
confidence: 99%